EFEKTIFITAS PERATURAN KAMPUNG BEBAS ASAP ROKOK DI RW 11 MENDUNGAN, GIWANGAN, UMBULHARJO, YOGYAKARTA - Gunawan Gunawan (Jurnal Sosiologi Reflektif, 2016)
The formation of free-tobacco village has aimed to control smoking behavior among the village members. The title of free-tobacco village does not necessarily mean prohibit all village members to smoke, instead it limits them in terms of time and place to smoke. The main goal of this rule is to avoid the danger of tobacco for those who are not smoking. This is more related to the right of anyone to have a fresh air without any smoke pollution. The main issue of this article is to examine the effectiveness of the rule with considering on how that rule is being form and implemented in RW 11, Mendungan Village. This article employs social behaviorism theory in examining the behavior of smokers in the village. Social behaviorism theory emphasis on individual factor and its interactions toward others. This interaction process becomes distinctive character compare to psychological behaviorism. To collect data, researcher uses observations, interviews, and documentations. Collected data, then, is being analyzed using descriptive qualitative approach. Results show that free-tobacco village is formed mainly to preserve the health of villagers and to protect those who are not consume tobacco from the danger of smoking. Intensive socialization through placing non-smoking areas in most all public facilities and giving social punishments, particularly in a form of warning are effective enough to control total consumption of tobacco in the village. After the socialization period is over, those who broke the rule will be fied. Collected fies will be used to support social activities of the villagers